2017
DOI: 10.1002/jip.1491
|View full text |Cite
|
Sign up to set email alerts
|

Change and stability in offender, behaviours, and incident‐level characteristics of mass public shootings in the United States, 1984–2015

Abstract: For the last 40 years, the general profile of mass public shooters has enjoyed enduring consensus by experts, and as a result, it has remained static over this time. However, a recent string of mass public shootings perpetrated by “atypical” offenders bring into question the stability of the characteristics, motivations, and methods employed by these offenders. The goal of this study is to examine the stability and change of these characteristics and behaviors over the last 32 years (1984–2015). Using an open‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 27 publications
(70 reference statements)
0
44
0
Order By: Relevance
“…This database mainly overlaps with the Mother Jones collection, although with some notable differences. Similarly, Lemieux () found that AWs were used in 26% of 73 public mass murder incidents he studied from 1983 to 2013, and Capellan and Gomez () estimated that “rifles or assault rifles” were used in approximately 23% of 206 mass murders or attempted mass murders they documented from 2000 to 2015. Both of these AW estimates are similar to that of Krouse and Richardson ().…”
mentioning
confidence: 96%
“…This database mainly overlaps with the Mother Jones collection, although with some notable differences. Similarly, Lemieux () found that AWs were used in 26% of 73 public mass murder incidents he studied from 1983 to 2013, and Capellan and Gomez () estimated that “rifles or assault rifles” were used in approximately 23% of 206 mass murders or attempted mass murders they documented from 2000 to 2015. Both of these AW estimates are similar to that of Krouse and Richardson ().…”
mentioning
confidence: 96%
“…Some conclude that the frequency of mass shooting homicides has increased (Bjelopera, Bagalman, Caldwell, Finklea, & McCallion, ; Follman, Pan, & Aronsen, ; Huff‐Corzine et al., ). Capellan and Gomez (; see also Blair & Schweit, ; Silva, ) found that public mass shootings doubled from the 1984–1999 period to the 2000–2016 period. Others have countered that the number of mass shootings each year is barely a handful and that this number has remained stable.…”
mentioning
confidence: 99%
“…In our analysis we focused on events with four or more people killed, since high-fatality incidents are most likely to receive significant amounts of national media attention (Duwe, 2000; Silva & Capellan, 2019), and are most likely to foment changes to public policy (Fox & DeLateur, 2014; Schildkraut & Elsass, 2016). Selecting events based on an arbitrary number of fatalities has been criticized, since people who were wounded in an attack were clearly meant to be killed by the perpetrator but instead managed to survive the attack (Capellan & Gomez, 2018; Lott & Landes, 2000). In addition, “thwarted” attacks, where the perpetrator apparently meant to shoot many people but was prevented from doing so by some means (such as bystander interference, for example) may provide information on whether or not various potential intervention measures are actually efficacious.…”
Section: Discussionmentioning
confidence: 99%
“…Even the FBI Supplementary Homicide Reports are incomplete in their details and in their tally of multiple-victim shootings (Huff-Corzine et al, 2014; Towers et al, 2015). Researchers currently must rely on media reports and online documents to attempt to fill in the gaps of the official record (Capellan & Gomez, 2018; Parkin & Gruenewald, 2017), and under-reporting by the media of low-fatality events can bias the detection efficiency for such events (Duwe, Kovandzic, & Moody, 2002; Schildkraut, Elsass, & Meredith, 2018; Silva & Capellan, 2019). In addition, the further back in time one goes, the more likely low-fatality events will escape notice.…”
Section: Discussionmentioning
confidence: 99%